A new species of the genus Colopalpus Pritchard and Baker (Trombidiformes: Tenuipalpidae) from China, with ontogenetic patterns in chaetotaxy - Xu, Yun; Zhang, Fei-Ping (Zootaxa, 2021)
A new species, Colopalpus hibiscus sp. nov. (Acari: Tenuipalpidae) is described from Hibiscus in Hainan province, China. The ontogenetic changes in the idiosoma and leg chaetotaxy on adults (female and male) and immature stages of this new species are presented. A key to species of Colopalpus is also provided.